Substitution urethroplasty for the treatment of male urethral stricture: Outcomes in an Australian center. Issue 4 (7th May 2019) - Al‐Hakeem, Yasser; Chung, Amanda; Chung, Belinda; Tse, Vincent
Abstract: Objective: This study evaluated the outcomes of urethroplasty performed in male patients by a single surgeon. Methods: A retrospective review of male patients who underwent substitution urethroplasty by a single surgeon was performed. Baseline and perioperative parameters were recorded. Follow‐up involved a pericatheter urethrogram at 3 weeks, a flow study at 8 weeks, and cystoscopic calibration within 6 to 12 months. Patient satisfaction was assessed using the Patient Global Impression of Improvement questionnaire. Primary outcome was functional success, as defined by no need for further intervention. Secondary outcomes were complications, patient satisfaction, and factors associated with stricture recurrence. Results: Sixty male patients were included; two were lost to follow‐up. Median patient age was 47 years (range 17–83 years). Mean stricture length was 5 cm (range 1.5–18 cm). Urethroplasty was performed using buccal mucosa graft repair in 53 patients (92%), flap repair in three patients (5%), and a combination of both techniques in two patients (3%). All complications were Clavien–Dindo Grade I to III, recorded in 20 patients (34%). At a mean follow‐up of 50 months (range 12–124 months), functional success was evident in 90% of patients. Cystoscopic calibration at 6 to 18 months was performed in 28 patients (49%). Most patients (93%) reported a better quality of life after the procedure. Oral complications were low grade and uncommon (6%). Stricture recurrence was not related to age, stricture length, or etiology (all P  > 0.05). Conclusions: Substitution urethroplasty has a high success rate, durable response, and high patient satisfaction. Standardization of surveillance protocol after urethroplasty is recommended.